2012
DOI: 10.1371/journal.pone.0044136
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Growth Hormone Levels and Nonalcoholic Fatty Liver Disease: A Cross-Sectional Study

Abstract: Growth hormone (GH) is an important regulator of metabolism and body composition. GH deficiency is associated with increased visceral body fat and other features of the metabolic syndrome. Here we performed a cross-sectional study to explore the association of GH levels with nonalcoholic fatty liver disease (NAFLD), which is considered to be the hepatic manifestation of the metabolic syndrome. A total of 1,667 subjects were diagnosed as NAFLD according the diagnostic criteria, and 5,479 subjects were defined a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 29 publications
1
46
0
1
Order By: Relevance
“…In a large cross-sectional study including 1667 patients diagnosed with NAFLD and 5479 controls, random GH levels were lower in the NAFLD group (0.02 vs 0.11 ng/ml) (56). GH levels were negatively correlated with other features of the metabolic syndrome and the NAFLD cohort was significantly older.…”
Section: Oestrogensmentioning
confidence: 93%
“…In a large cross-sectional study including 1667 patients diagnosed with NAFLD and 5479 controls, random GH levels were lower in the NAFLD group (0.02 vs 0.11 ng/ml) (56). GH levels were negatively correlated with other features of the metabolic syndrome and the NAFLD cohort was significantly older.…”
Section: Oestrogensmentioning
confidence: 93%
“…In one cohort of growth hormone-deficient patients, 77% presented with NAFLD (Nishizawa et al 2012). Conversely, individuals with NAFLD were found to have significantly lower growth hormone levels than controls (Xu et al 2012). Cushing's syndrome is present in 0.00025% of the general population, yet exists in 1.4% of type 2 diabetics with 3.4% displaying hypercortisolemia (Steffensen et al 2016).…”
Section: Introductionmentioning
confidence: 97%
“…Low levels of growth hormone (GH) in the general population associate with NAFLD (2). Multi–single nucleotide polymorphism analyses of genome-wide association study have revealed 18 single nucleotide polymorphisms in the GH pathway that relate to the development and progression of NAFLD (3).…”
Section: Introductionmentioning
confidence: 99%
“…Also, patients with GH receptor (GHR) loss of function (Laron syndrome) exhibit NAFLD (4). Likewise, cessation of GH treatment in GH-deficient (GHD) children after achieving adult height leads to development of NAFLD and dyslipidemia in 29% of patients surveyed 10 years after therapy (2). Importantly, reductions in circulating GH (2,5) or its mediator, IGF-1 (68), associate with NAFLD even after adjusting to BMI (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation